AN ANALYTICAL STUDY OF THE ROLE OF WOMEN OF HARYANA IN THE INDIAN FREEDOM STRUGGLE - Anju; Devi, Mamta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Against British colonialism, Indians across India united and challenged the world’s most powerful imperialist power by forgetting the differences of language, religion, caste, region, rich-poor and gender. After a long and tough struggle and sacrifices, we achieved independence. The people of Haryana also participated enthusiastically in this long struggle. In which women undoubtedly suffered more. Because their role in the national freedom struggle was multifaceted. Extensive research has been done on various aspects of the national movement and research work is going on on many incidents. But still understanding the role of Haryana in the national movement, especially the role of women of Haryana region, is an untouched area. The purpose of this research article is to fill this research gap and to do a systematic historical analysis of the participation of women of Haryana in the national freedom movement. The research material for this research article has been taken from various books related to history, freedom struggle, women’s movements and women’s organizations, articles published in various journals and magazines and research articles etc. from secondary sources.